Analysis Of Water Mimosa (Neptunia Plena (L.) Benth.) Density As Water Pollution Level Bioindicators In Jalan Karya Baru, Palembang, South Sumatra - Fitri, Fitri (Universitas Hang Tuah, 2024)
One of commonly found flora in swamps is water mimosa (Neptunia plena (L.) Benth.). Swamp is low land ecological system filled with standing water. This study aims to measure approximate water pollution level based on water mimosa (Neptunia plena (L.) Benth.) density using biometering to be used as public information to maintain and manage swamp water quality. This study showed dissolved oxygen content was 23.6, 24.64, and 25.05 at Station I, II, and III respectively. The pH at Station I, II, and III was 6.48, 6.50, and 6.47 respectively. The clarity was 0.18 m, 0.47 m, and 1.12 m at Station I, II, and III respectively, averaging at 0.59 m. Highest depth was observed at Station II (2.2 m), while lowest depth was observed at Station I (1.5 m). bserved at Station